Benign biliary strictures treated with biodegradable stents in patients with surgically altered anatomy using double balloon enteroscopy. (2nd October 2020) - Lindström, Outi; Udd, Marianne; Rainio, Mia; Nuutinen, Hannu; Jokelainen, Kalle; Kylänpää, Leena
Abstract: Objectives: Surgically altered anatomy complicates endoscopical procedures of pancreatobiliary tree. Biliary or hepaticojejunal anastomosis strictures have been managed using percutaneous transhepatic or double balloon enteroscopy (DBE) techniques with multiple plastic stents, or fully covered self-expandable metal stents. We report the first seven cases with surgically altered anatomy treated with biodegradable stents with DBE. Materials and methods: Seven cases with altered anatomy, all with Roux-en-Y hepaticojejunostomy (HJ), were treated for HJ anastomosis strictures (3 cases) and intrahepatic biliary stricture (4 cases). Fujifilm DB enteroscope with a 200 cm long and 3.2 mm wide working channel was used. Balloon dilatations were first performed and then 1–3 biodegradable stents were deployed with a pusher over a guidewire. Results: Two patients had HJ due to liver resections, one due to biliary injury in cholecystectomy and four due to liver transplantation because of primary sclerosing cholangitis (PSC). Median duration of the procedures was 56 min. Deployment of the stents took less than 20 min per patient. There were no stent or cholangiography related adverse events, but one patient required endotracheal intubation for nose bleeding caused by the placement of nasopharyngeal tube. Two PSC patients had recurrent cholangitis in the follow up. There was one stent migration in 90 day follow up. With all the HJ anastomotic strictures resolution of strictures seemed to be achieved. Conclusions: Treatment of biliary or anastomosis strictures in altered anatomy is complex and time consuming. The biodegradable stent, which can be passed through working channel of a long enteroscope, seems promising in the treatment of these strictures. The benefit is that no stent removal is needed.